Mass Media and Religious Culture of the Audiences; Suggesting a Useful Approach to Media Productions for Children - Nasser Bahonar (Taḥqīqāt-i Farhangī-i Īrān, 2008)
The religious program of mass media exclusively produced for children have had a significant growth in recent years. The artistic expression of stories related to the life of the great prophets and to the history of Islam as well as taking advantage of theatrical literature in religious occasions can herald successes in this neglected field. But, what is questionable in national religious policies in that why who are involved in the religious education of children whether in traditional media (family, mosques, religious communities, etc) or in modern media (textbooks, press, radio and television) do not follow an integrated and coherent policy based on a proved theoretical view of religious communications. In fact, this question results from the same old opposition between audience-oriented and media-oriented approaches in communications as well as the opposition between cognitivism and other approaches in psychology. The findings of the field of study conducted by the author along with psychological achievements of cognitivism in human communications and cultural audience-oriented approaches, especially reception theory in mass communications can solve some existing difficulties in the formulation of religious messages. Drawing upon the above mentioned theoretical schools, this article tries to introduce a useful approach to producing religious programs for children and describes the main tasks of mass media in this field accordingly.